PENERAPAN PAIKEM MENGGUNAKAN MEDIA GAME INTERAKTIF DALAM MENINGKATKAN MINAT BELAJAR PAI DI SMP KARTIKA IV-1 SURABAYA - Muhammad Rasikhul Islam; Yoga Surya Pramahdi; Yustia Nengseh; Muhammad Yusron Maulana El-Yunusi (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
The problem with education lately is the low quality of learning, students are not given the freedom to develop thinking skills. They are detected by learning systems and methods that have an equal structure for each student, even though each student has different characteristics and intelligence, and different ways of thinking. This type of research is a type of qualitative research, namely the structure of the activity of processing information under reasonable conditions in the daily behavior of an object and then connected with a problem in theoretical and practical perspectives.The application of the PAIKEM Method using interactive game media is very effective, this teaching material is able to change some boring old ways of learning into new ways that are fun.Students'' interest in participating in Islamic Religious Education lessons is also increasing, this is evidenced by the increased liveliness and competitive spirit of students in participating in lessons.The application of PAIKEM using interactive game media is felt to be running according to the expectations and desired goals, namely being able to increase student interest in PAI lessons students are more active and enthusiastic when implementing Islamic Religious Education learning. The attitude of competition and mutual interaction between students grows and develops in a more positive direction.